2013
DOI: 10.1107/s160053681302059x
|View full text |Cite
|
Sign up to set email alerts
|

trans-Acetyldicarbonyl(η5-cyclopentadienyl)[tris(furan-2-yl)phosphane-κP]molybdenum(II)

Abstract: Key indicators: single-crystal X-ray study; T = 173 K; mean (C-C) = 0.005 Å; R factor = 0.035; wR factor = 0.075; data-to-parameter ratio = 17.3.The title compound, [Mo(C 5 H 5 )(C 2 H 3 O)(C 12 H 9 O 3 P)(CO) 2 ], was prepared by reaction of [Mo(C 5 H 5 )(CO) 3 (CH 3 )] with tris(furan-2-yl)phosphane. The Mo II atom exhibits a fourlegged piano-stool coordination geometry with the acetyl and phosphine ligands trans to each other. The O atom of the acetyl ligand points down, away from the Cp ring. In the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Complexes (1) and (2) both have structures where the oxygen atom of the acetyl group points toward the cyclopentadienyl (Cp) ring. This orientation is also consistent with the majority of crystal structures of related complexes, with the exception of the recently reported tri(2-furyl)phosphine derivative, in which the acetyl group points away from the Cp ring, enabling intermolecular OÁ Á ÁH-C interactions with the furyl group of a neighboring molecule (Whited et al, 2013).…”
Section: Structural Commentarysupporting
confidence: 88%
See 1 more Smart Citation
“…Complexes (1) and (2) both have structures where the oxygen atom of the acetyl group points toward the cyclopentadienyl (Cp) ring. This orientation is also consistent with the majority of crystal structures of related complexes, with the exception of the recently reported tri(2-furyl)phosphine derivative, in which the acetyl group points away from the Cp ring, enabling intermolecular OÁ Á ÁH-C interactions with the furyl group of a neighboring molecule (Whited et al, 2013).…”
Section: Structural Commentarysupporting
confidence: 88%
“…We have developed an interest in the solid-state structural properties of a series of piano-stool molybdenum acetyl complexes derived from migratory insertion with various phosphines, with the goal of understanding how modification ISSN 1600-5368 of the phosphine substituents affects ground-state structure as well as solid-state packing. Recently, we reported an unusual example where orientation of the acetyl group in the solid state can be changed by introduction of furyl substituents on the phosphine ligand (Whited et al, 2013). In this study, the structures obtained for dimethylphenylphosphine, [Mo(C 5 H 5 )(P(CH 3 ) 2 (C 6 H 5 ))(CO) 2 (COCH 3 )] (1), and ethyldiphenylphosphine,…”
Section: Chemical Contextmentioning
confidence: 96%
“…We have shown that the steric bulk of the phosphine substituents impacts the molecular structure of the insertion product in predictable ways, primarily evidenced through the Mo-P bond lengths and P-Mo-C bond angles (Whited et al, 2012, consistent with earlier findings on reactivity. We have also shown that the use of tri(2-furyl)phosphine, which features heteroatoms as potential hydrogen-bond acceptors, leads to an unusual structure where the acetyl is oriented away from the Cp ring rather than toward it as in other cases (Whited et al, 2013).…”
Section: Chemical Contextmentioning
confidence: 84%
“…10 students total) have used methyldiphenylphosphine successfully (quantitative yield by 31 P NMR and >60% recovered yields). As an indication of the generality of the synthesis, several student groups have used different phosphines in parallel independent-study style experiments. , …”
Section: Methodsmentioning
confidence: 99%